Exosomes as Pleiotropic Players in Pancreatic Cancer - Laura De Lellis; Rosalba Florio; Maria Cristina Di Bella; Davide Brocco; Francesca Guidotti; Nicola Tinari; Antonino Grassadonia; Rossano Lattanzio; Alessandro Cama; Serena Veschi (Biomedicines, 2021)
Pancreatic cancer (PC) incidence is rising and due to late diagnosis, combined with unsatisfactory response to current therapeutic approaches, this tumor has an extremely high mortality rate. A better understanding of the mechanisms underlying pancreatic carcinogenesis is of paramount importance for rational diagnostic and therapeutic approaches. Multiple lines of evidence have showed that exosomes are actively involved in intercellular communication by transferring their cargos of bioactive molecules to recipient cells within the tumor microenvironment and systemically. Intriguingly, exosomes may exert both protumor and antitumor effects, supporting or hampering processes that play a role in the pathogenesis and progression of PC, including shifts in tumor metabolism, proliferation, invasion, metastasis, and chemoresistance. They also have a dual role in PC immunomodulation, exerting immunosuppressive or immune enhancement effects through several mechanisms. PC-derived exosomes also induce systemic metabolic alterations, leading to the onset of diabetes and weight loss. Moreover, exosomes have been described as promising diagnostic and prognostic biomarkers for PC. Their potential application in PC therapy as drug carriers and therapeutic targets is under investigation. In this review, we provide an overview of the multiple roles played by exosomes in PC biology through their specific cargo biomolecules and of their potential exploitation in early diagnosis and treatment of PC.